Aspekty chování spotřebitelů při nákupu potravin - Hes, Aleš; Šálková, Daniela (Communication Today, 2025)
There have been many changes in internal trade during last ten years. Businessmen make use of not only well known instruments as it is obvious in the environment of strong competition. They try to diversify business activities to sales programmes in order to meet the customer’s needs regarding the quality, ethics and information transfer. Customers got used to a convenient offer of consumer goods and adjust their behaviour accordingly to it. The retailers approach this phenomenon in different ways depending on their ability to understand and make advantage of these behaviour changes. This contribution was processed within the Research Project of MSM 6046070906 “The economics of Czech agricultural resources and then effective use within multifunctional systems of agriculture and food“, Faculty of Economics and Management, Czech University of Life Sciences in Prague